Water-resistant chip potting glue and preparation method thereof
By adopting water-resistant chip potting glue with specific component ratios and prepolymer preparation methods, the problem of difficulty in meeting diverse properties in the prior art is solved, and efficient mechanical, waterproof, aging resistance and corrosion resistance are achieved, and the application field is expanded.
Patent Information
- Application Number
- CN202411505312.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-10-28
AI Technical Summary
When facing the demand for high-performance electronic products, existing chip potting glues are difficult to meet the diverse properties of heat resistance, aging resistance, temperature resistance, corrosion resistance, UV radiation resistance, waterproof and moisture resistance.
A water-resistant chip potting agent consisting of components A and components B is used. Component A includes composite polyols, plasticizers, antioxidants, leveling agents, fillers and additives. Component B includes isocyanate, isocyanate prepolymer, catalysts and defoaming agents. Through specific component ratios and prepolymer preparation methods, polymer network structure is formed to improve the mechanical, waterproof, aging resistance and corrosion resistance of potting glue.
On the basis of maintaining excellent mechanical properties and waterproof properties, the corrosion resistance, aging resistance and stability of chip potting are significantly improved, meeting the needs of diverse performances, and expanding application fields and environment.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present application relates to the field of potting adhesives, and in particular to a water-resistant chip potting adhesive and a preparation method thereof. Background Art
[0002] In the modern electronics industry, with the rapid development of integrated circuit technology, the miniaturization and integration of chips are constantly improving, and the requirements for chip packaging materials are becoming increasingly stringent. Traditional packaging methods can no longer meet the needs of high-performance electronic products, especially in terms of reliability, thermal management, and environmental adaptability. As one of the important packaging materials, chip potting glue provides physical protection for the chip while ensuring its electrical performance, preventing moisture, dust and other external factors from damaging the chip.
[0003] Chip potting glue is precisely poured into the inside of the device containing electronic components and circuits by manual or mechanical means, and solidified under certain temperature conditions (normal temperature or heating) to form a thermosetting polymer insulating material with excellent performance. Its main function is to provide bonding, sealing, potting and coating protection for electronic components, which is crucial to ensure the reliability and extend the service life of electronic products. Early chip potting glue mostly used epoxy resin system because of its good electrical properties, mechanical strength and chemical resistance. However, with the advancement of technology, a single epoxy resin system has been difficult to meet higher-level needs. For example, due to the large amount of heat generated during the operation of the chip, higher requirements are placed on the heat resistance, aging resistance and temperature stability of the potting material; at the same time, in order to adapt to a wider range of use environments, such as automotive electronics, aerospace and other fields, the potting glue also needs to have better corrosion resistance, UV radiation resistance and waterproof and moisture-proof properties, but the performance diversity of existing potting glue products is poor. Usually, in order to achieve better sealing effect and mechanical properties, it is impossible to simultaneously meet the requirements of existing products for the diverse performance of potting glue.
[0004] Therefore, in order to solve the above problems, the present application provides a water-resistant chip potting glue and a preparation method thereof. The water-resistant chip potting glue prepared in the present application can effectively improve the corrosion resistance, aging resistance and stability of the chip potting glue while maintaining excellent mechanical properties and waterproof properties of the potting glue. It can effectively meet the needs of existing scientific and technological products for the diverse performance of potting glue, expand the application fields and environments of potting glue and its potted chips, and has very excellent application prospects. Summary of the invention
[0005] In order to solve the above problems, the first aspect of the present application provides a water-resistant chip potting glue, which is composed of component A and component B; the raw materials of component A, in parts by mass, are: 60-80 parts of complex polyol, 4-12 parts of plasticizer, 0.5-1.5 parts of antioxidant, 1.5-3 parts of leveling agent, 5-15 parts of filler, and 5-10 parts of auxiliary agent;
[0006] The raw materials of the component B are, by weight: 45-55 parts of isocyanate, 10-15 parts of isocyanate prepolymer, 0.5-1.2 parts of catalyst, and 1-1.5 parts of defoamer.
[0007] As a preferred solution, the mass ratio of component A to component B is (1.1-1.2):(0.7-0.9).
[0008] As a preferred solution, the mass ratio of the complex polyol to the auxiliary agent is (65-75): (7.5-9.5).
[0009] As a preferred solution, the mass ratio of the complex polyol, plasticizer and filler is (65-75): (6-10): (8-14).
[0010] As a preferred solution, the mass ratio of the complex polyol, plasticizer and filler is (68-72): (6-8): (9-12).
[0011] As a preferred solution, the complex polyol is a composition of propylene oxide-ethylene oxide copolyether glycol, polytetramethylene oxide ether glycol and polyurea polyol.
[0012] As a preferred solution, the mass ratio of the propylene oxide-ethylene oxide copolyether glycol, polytetramethylene oxide ether glycol and polyurea polyol is (4-5): (1.4-2): (0.5-1).
[0013] As a preferred solution, the mass ratio of the propylene oxide-ethylene oxide copolyether glycol, polytetramethylene oxide ether glycol and polyurea polyol is (4.6-4.8): (1.6-1.8): (0.6-0.8).
[0014] As a preferred solution, the number average molecular weight of the propylene oxide-ethylene oxide copolyether glycol is 3500~4800Da.
[0015] As a preferred solution, the hydroxyl value of the propylene oxide-ethylene oxide copolyether glycol is 20-32 mgKOH / g.
[0016] As a preferred solution, the number average molecular weight of the tetrahydrofuran ether diol is 1500~2200Da.
[0017] As a preferred solution, the hydroxyl value of the tetrahydrofuran ether diol is 30-35 mgKOH / g.
[0018] As a preferred solution, the polyurea content of the polyurea polyol is 15-20%.
[0019] As a preferred solution, the viscosity of the polyurea polyol is 3000-3500 mPa·s at 25°C.
[0020] As a preferred solution, the plasticizer is at least one of dioctyl phthalate, trioctyl citrate and triethyl citrate.
[0021] As a preferred solution, the plasticizer is dioctyl phthalate or triethyl citrate.
[0022] As a preferred solution, the antioxidant is at least one of antioxidant 1010, antioxidant 1076, and antioxidant 1035.
[0023] As a preferred solution, the antioxidant is antioxidant 1035.
[0024] As a preferred solution, the leveling agent is at least one of BYK-306, BYK-359, BYK-346, BYK-323 and DC-62.
[0025] As a preferred solution, the leveling agent is BYK-306.
[0026] As a preferred solution, the filler is a composition of sericite powder and aluminum oxide.
[0027] As a preferred solution, the mass ratio of the sericite powder to alumina is (2-3): (1.2-1.6).
[0028] As a preferred solution, the average particle size of the sericite powder is 1-2 μm; the average particle size of the aluminum oxide is 20-35 nm.
[0029] As a preferred solution, the auxiliary agent is methyl hydrogen polysiloxane.
[0030] As a preferred solution, the hydrogen content of the methyl hydrogen polysiloxane is 0.8-2%.
[0031] As a preferred solution, the methyl hydrogen polysiloxane is a composition of methyl hydrogen polysiloxane with a hydrogen content of 0.9-1% and methyl hydrogen polysiloxane with a hydrogen content of 1.55-1.8%.
[0032] As a preferred solution, the mass ratio of the methyl hydrogen polysiloxane with a hydrogen content of 0.9-1% and the methyl hydrogen polysiloxane with a hydrogen content of 1.55-1.8% is (4-4.2): (1-1.2).
[0033] The methyl hydrogen polysiloxane added in the present application as an auxiliary agent can effectively improve the curing effect of the chip potting glue, and enhance its mechanical, aging and waterproof properties. The combination scheme of adding methyl hydrogen polysiloxane with different hydrogen contents can realize a certain degree of cross-linking dehydrogenation reaction by controlling the hydrogen-containing methyl hydrogen polysiloxane under the action of a catalyst. The existence of this reaction can effectively increase the molecular cross-linking tightness in the chip potting glue system, enhance the construction of the three-dimensional molecular chain network structure inside the potting glue, and the reaction does not rely on the action of oxygen, and can be directly cured inside without relying on the curing guidance of the potting glue surface, so that the chip potting glue can be realized from the inside to the outside of the synchronous deep curing during the curing period, so that the internal network structure of the potting glue tends to be consistent with the tightness, and then in the penetration process of water molecules and free groups, the penetration and free speed inside the potting glue is greatly reduced, the resistance of penetration and active reaction is improved, and the content of water molecules and corrosion molecules that rely on water molecules to invade inside the potting glue is reduced, and then on the basis of ensuring excellent mechanical properties, the potting glue itself is also enhanced. Waterproof, aging resistance and corrosion resistance and other properties.
[0034] On the other hand, if the overall hydrogen content of methyl hydrogen polysiloxane is too high, it will lead to too fast dehydrogenation cross-linking reaction, especially the curing speed of the surface part of the potting glue is too fast, the degree of cross-linking is high, and the internal hydrogen cannot be removed in time, resulting in blistering, cracking and increased internal pores of the potting glue, which greatly affects the mechanical, aging corrosion resistance and waterproof properties of the potting glue. When the overall hydrogen content is low, it will greatly reduce the active cross-linking sites inside the potting glue, weaken the activity of dehydrogenation cross-linking, and then fail to achieve partial entanglement of the molecular chain network, thereby reducing the internal intermolecular force, and affecting the intermolecular strength, water molecules and free radical penetration rate.
[0035] As a preferred solution, the isocyanate is a combination of diphenylmethane diisocyanate and cyclohexylmethane diisocyanate.
[0036] As a preferred solution, the mass ratio of diphenylmethane diisocyanate to cyclohexylmethane diisocyanate is (3-4):(0.8-1.2).
[0037] As a preferred scheme, the preparation method of the isocyanate prepolymer comprises the following steps: S1: vacuum dehydrating tripropylene glycol at 120-130°C for 1.5-2h, then adding polymethylene polyphenyl isocyanate, keeping warm at 80-90°C with stirring, keeping warm for reaction for 2h, cooling to 60-65°C and discharging to obtain a pre-reaction material; S2: adding the pre-reaction material to deionized water, adding citric acid and succinic anhydride, then heating to 60-70°C and keeping warm for 1.5-2h, adding a titanate coupling agent, continuing to keep warm at 100-120rpm with stirring for 0.5-1h, discharging after completion, and obtaining the pre-reaction material after dehydration.
[0038] As a preferred solution, the mass ratio of tripropylene glycol to polymethylene polyphenyl isocyanate is (2.6-2.8): (1.8-2.2).
[0039] As a preferred solution, the mass ratio of the pre-reaction material, citric acid, succinic anhydride and titanate coupling agent is (10-12): (0.4-0.6): (1.5-2): (0.2-0.25).
[0040] As a preferred solution, the titanate coupling agent is triisostearyl isopropyl titanate.
[0041] The above-mentioned isocyanate prepolymer added in the present application and the specific composite polyol composition added can effectively improve the mechanical, waterproof, aging resistance and other properties of the chip potting glue. The addition of isocyanate prepolymer can not only assist in the construction of the main chain molecular chain participating in the internal network structure of the potting glue, but also promote the cross-linking entanglement phenomenon of the internal molecular chain through the long molecular chain and the multi-branched molecular chain structure, thereby increasing the cohesive force between the internal molecular chain and the molecule, and effectively enhancing the mechanical properties; on the other hand, the guiding effect of the multi-branched chain can effectively enhance the internal bonding degree of the filler particles, realize the adhesion effect with the surface of the filler particles, and then reduce the pore size of the particle pores formed by the filler particles in the potting glue, enhance the stability of the filler particles in the pores, reduce the offset phenomenon inside the potting glue, and then obtain excellent mechanical properties and thermal properties, while avoiding the beneficial effect of large pores on water molecule penetration and free group mobility efficiency, thereby helping to maintain good waterproof, aging corrosion resistance and other properties.
[0042] As a preferred solution, the catalyst is dibutyltin dilaurate or stannous octoate.
[0043] As a preferred solution, the defoaming agent is any one of the organosilicon defoaming agents.
[0044] The second aspect of the present application provides a method for preparing the above-mentioned water-resistant chip potting glue, which specifically includes the following steps: S1: Weigh the raw materials required for component A and component B respectively, mix and stir them evenly in different mixing containers at a temperature of 25~35°C and a stirring speed of 60~80rpm to obtain component A and component B; S2: Mix component A and component B in a clean container according to the mass ratio, stir them evenly at a temperature of 25~35°C and a stirring speed of 200~250rpm, and after mixing evenly, place the mixture in a vacuum environment for degassing treatment, the vacuum degree is -0.09~-0.10MPa, and the degassing time is 10~15min; S3: After degassing is completed, pour the mixture into the chip components to be potted, heat it to 70~85°C and cure it for 3~4h to obtain the chip potting glue.
[0045] The beneficial effects of this application are:
[0046] 1. A water-resistant chip potting glue provided in the present application can effectively improve the corrosion resistance, aging resistance and stability of the chip potting glue while maintaining excellent mechanical properties and waterproof properties of the potting glue. It can effectively meet the needs of existing scientific and technological products for the diverse performance of potting glue, expand the application field and environment of potting glue and its potted chips, and has very excellent application prospects.
[0047] 2. A water-resistant chip potting glue provided in the present application, in which methyl hydrogen polysiloxane is added as an auxiliary agent to effectively improve the curing effect of the chip potting glue, and enhance its mechanical, aging resistance and waterproof properties; the combination scheme of adding methyl hydrogen polysiloxanes with different hydrogen contents can achieve a certain degree of cross-linking dehydrogenation reaction by controlling the hydrogen-containing methyl hydrogen polysiloxane under the action of a catalyst. The existence of this reaction can effectively increase the molecular cross-linking tightness in the chip potting glue system, enhance the construction of the three-dimensional molecular chain network structure inside the potting glue, and the reaction does not rely on the action of oxygen, and can be directly cured inside without relying on the curing guidance of the potting glue surface, so that the chip potting glue can be achieved during the curing period. Deep simultaneous curing from the inside to the outside, so that the internal network structure of the potting glue from top to bottom tends to be consistent in tightness, and then in the process of water molecules and free groups penetrating, their penetration and free speed inside the potting glue is greatly reduced, and the resistance to penetration and active reactions is increased.
[0048] 3. The water-resistant chip potting glue provided in the present application, the added isocyanate prepolymer and the added specific composite polyol composition can effectively improve the mechanical, waterproof, aging resistance and other properties of the chip potting glue. The addition of isocyanate prepolymer can not only assist in the construction of the main chain molecular chain participating in the internal network structure of the potting glue, but also promote the cross-linking and entanglement of the internal molecular chain through the long molecular chain and multi-branched molecular chain structure, thereby increasing the cohesive force between the internal molecular chain and the molecules, and effectively enhancing the mechanical properties; on the other hand, the guiding effect of the multi-branched chain can effectively enhance the degree of adhesion of the filler particles inside, achieve adhesion with the surface of the filler particles, and then reduce the pore size of the particle pores formed by the filler particles inside the potting glue, thereby reducing its amplitude influence on the mechanical, waterproof, aging and corrosion resistance and other properties of the potting glue. DETAILED DESCRIPTION
[0049] The following will further explain and demonstrate the technical solutions in the above invention content of this application in the form of specific implementation schemes. The following embodiments are only practical examples used to illustrate and explain the contents of the technical solutions in the specification, and should not limit the scope of the claims to be protected by this application. All technical products based on the technical solutions described in the invention content of this application should be included in the scope to be protected by this application.
[0050] In the following examples, unless otherwise specified, the raw materials are all commercially available products, or can be prepared by methods well known to those skilled in the art.
[0051] Example 1
[0052] Embodiment 1 The first aspect provides a water-resistant chip potting adhesive, which is composed of component A and component B; component A, in parts by mass, comprises: 70.5 parts of complex polyol, 7.6 parts of plasticizer, 1.2 parts of antioxidant, 2.4 parts of leveling agent, 9.6 parts of filler, and 8.8 parts of auxiliary agent;
[0053] The raw materials of component B, calculated by mass, are: 49.6 parts of isocyanate, 11.4 parts of isocyanate prepolymer, 0.9 parts of catalyst, and 0.8 parts of defoaming agent.
[0054] The mass ratio of component A to component B is 1.12:0.88.
[0055] The composite polyol is a composition of propylene oxide-ethylene oxide copolyether glycol, polytetramethylene ether glycol and polyurea polyol, and the mass ratio of the three is 4.6:1.8:0.6.
[0056] The propylene oxide-ethylene oxide copolyether glycol has a number average molecular weight of 4600 Da and a hydroxyl value of 22 mgKOH / g, and is purchased from Dow Chemical under the model number of Voranol L4600.
[0057] The number average molecular weight of tetrahydrofuran ether diol is 2000 Da, and the hydroxyl value is 30 mgKOH / g. It is a PTMG2000 product purchased from BASF.
[0058] The polyurea polyol had a polyurea content of 19.2% and a viscosity of 3200 mPa·s at 25° C. It was purchased from Evonik Industries as a polyurea-modified 9151 product.
[0059] The plasticizer is dioctyl phthalate; the antioxidant is antioxidant 1035; and the leveling agent is BYK-306.
[0060] The filler is a composition of sericite powder and alumina, and the mass ratio of the two is 2.4:1.5.
[0061] The average particle size of the sericite powder is 1.8 μm; the average particle size of the aluminum oxide is 26 nm.
[0062] The auxiliary agent is a composition of methyl hydrogen polysiloxane with a hydrogen content of 0.98% and 1.66%, and the mass ratio of the two is 4.2:1.1. The methyl hydrogen polysiloxane with a hydrogen content of 0.98% was purchased from the corresponding hydrogen content model product sold by Shandong Longhui Chemical Co., Ltd.; the methyl hydrogen polysiloxane with a hydrogen content of 1.66% was purchased from the corresponding hydrogen content model product in the MHX series sold by Green Union (Jining) Chemical Technology Co., Ltd.
[0063] The isocyanate is a composition of diphenylmethane diisocyanate and cyclohexylmethane diisocyanate, and the mass ratio of the two is 3.6:1.1.
[0064] The preparation method of isocyanate prepolymer comprises the following steps, calculated by mass: S1: dehydrating 2.68 parts of tripropylene glycol in vacuum at 120°C for 2h, then adding 1.95 parts of polymethylene polyphenyl isocyanate, keeping warm at 85°C with stirring, keeping warm for reaction for 2h, cooling to 60°C and discharging to obtain a pre-reaction material; S2: adding 10.6 parts of the pre-reaction material to 220 parts of deionized water, adding 0.45 parts of citric acid and 1.68 parts of succinic anhydride, then heating to 65°C and keeping warm for 2h, adding 0.22 parts of titanate coupling agent, continuing to keep warm and stirring at 100rpm for 1h, discharging after completion, and obtaining the product after dehydration.
[0065] The titanate coupling agent is triisostearyl isopropyl titanate.
[0066] The catalyst is dibutyltin dilaurate; the defoaming agent is BYK-028.
[0067] The second aspect of the present application provides a method for preparing the above-mentioned water-resistant chip potting glue, which specifically includes the following steps: S1: Weigh the raw materials required for component A and component B respectively, mix and stir them evenly in different mixing containers at a temperature of 30°C and a stirring speed of 80rpm to obtain component A and component B; S2: Mix component A and component B in a clean container according to the mass ratio, stir evenly at a temperature of 30°C and 240rpm, and after mixing evenly, place the mixture in a vacuum environment for degassing treatment, the vacuum degree is -0.09MPa, and the degassing time is 12min; S3: After degassing is completed, pour the mixture into the chip components to be potted, heat it to 80°C and cure it for 3.5h to obtain the chip potting glue.
[0068] Example 2
[0069] Embodiment 2 The first aspect provides a water-resistant chip encapsulant, which is composed of component A and component B; component A, in parts by mass, comprises: 74.5 parts of complex polyol, 6.2 parts of plasticizer, 1 part of antioxidant, 2.6 parts of leveling agent, 8.5 parts of filler, and 9.5 parts of auxiliary agent;
[0070] The raw materials of component B, calculated by mass, are: 49.6 parts of isocyanate, 11.4 parts of isocyanate prepolymer, 0.9 parts of catalyst, and 0.8 parts of defoaming agent.
[0071] The mass ratio of component A to component B is 1.16:0.82.
[0072] The composite polyol is a composition of propylene oxide-ethylene oxide copolyether diol, polytetramethylene ether diol and polyurea polyol, and the mass ratio of the three is 4.2:1.5:0.8.
[0073] The propylene oxide-ethylene oxide copolyether glycol has a number average molecular weight of 4600 Da and a hydroxyl value of 22 mgKOH / g, and is purchased from Dow Chemical under the model number of Voranol L4600.
[0074] The number average molecular weight of tetrahydrofuran ether diol is 2000 Da, and the hydroxyl value is 30 mgKOH / g. It is a PTMG2000 product purchased from BASF.
[0075] The polyurea polyol had a polyurea content of 19.2% and a viscosity of 3200 mPa·s at 25° C. It was purchased from Evonik Industries as a polyurea-modified 9151 product.
[0076] The plasticizer is dioctyl phthalate; the antioxidant is antioxidant 1035; and the leveling agent is BYK-306.
[0077] The filler is a composition of sericite powder and alumina, and the mass ratio of the two is 2.8:1.2.
[0078] The average particle size of the sericite powder is 1.8 μm; the average particle size of the aluminum oxide is 26 nm.
[0079] The auxiliary agent is a composition of methyl hydrogen polysiloxane with a hydrogen content of 0.98% and 1.66%, and the mass ratio of the two is 4.2:1.1. The methyl hydrogen polysiloxane with a hydrogen content of 0.98% was purchased from the corresponding hydrogen content model product sold by Shandong Longhui Chemical Co., Ltd.; the methyl hydrogen polysiloxane with a hydrogen content of 1.66% was purchased from the corresponding hydrogen content model product in the MHX series sold by Green Union (Jining) Chemical Technology Co., Ltd.
[0080] The isocyanate is a composition of diphenylmethane diisocyanate and cyclohexylmethane diisocyanate, and the mass ratio of the two is 3.6:1.1.
[0081] The preparation method of isocyanate prepolymer comprises the following steps, calculated by mass: S1: dehydrating 2.68 parts of tripropylene glycol in vacuum at 120°C for 2h, then adding 1.95 parts of polymethylene polyphenyl isocyanate, keeping warm at 85°C with stirring, keeping warm for reaction for 2h, cooling to 60°C and discharging to obtain a pre-reaction material; S2: adding 10.6 parts of the pre-reaction material to 220 parts of deionized water, adding 0.45 parts of citric acid and 1.68 parts of succinic anhydride, then heating to 65°C and keeping warm for 2h, adding 0.22 parts of titanate coupling agent, continuing to keep warm and stirring at 100rpm for 1h, discharging after completion, and obtaining the product after dehydration.
[0082] The titanate coupling agent is triisostearyl isopropyl titanate.
[0083] The catalyst is dibutyltin dilaurate; the defoaming agent is BYK-028.
[0084] The second aspect of the present application provides a method for preparing the above-mentioned water-resistant chip potting glue, which specifically includes the following steps: S1: Weigh the raw materials required for component A and component B respectively, mix and stir them evenly in different mixing containers at a temperature of 30°C and a stirring speed of 80rpm to obtain component A and component B; S2: Mix component A and component B in a clean container according to the mass ratio, stir evenly at a temperature of 30°C and 240rpm, and after mixing evenly, place the mixture in a vacuum environment for degassing treatment, the vacuum degree is -0.09MPa, and the degassing time is 12min; S3: After degassing is completed, pour the mixture into the chip components to be potted, heat it to 80°C and cure it for 3.5h to obtain the chip potting glue.
[0085] Comparative Example 1
[0086] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the water-resistant chip encapsulant is composed of component A and component B; the raw materials of component A, by mass parts, are: 64.3 parts of complex polyol, 7.6 parts of plasticizer, 1.2 parts of antioxidant, 2.4 parts of leveling agent, 9.6 parts of filler, and 3.3 parts of auxiliary agent;
[0087] The raw materials of component B, calculated by mass, are: 53.5 parts of isocyanate, 10.2 parts of isocyanate prepolymer, 0.8 parts of catalyst, and 0.8 parts of defoaming agent.
[0088] The mass ratio of component A to component B is 1:1.
[0089] Comparative Example 2
[0090] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the water-resistant chip encapsulant is composed of component A and component B; the raw materials of component A, by weight, are: 65.5 parts of complex polyol, 7.6 parts of plasticizer, 1.2 parts of antioxidant, 2.4 parts of leveling agent, 9.6 parts of filler, and 12.5 parts of auxiliary agent;
[0091] The raw materials of component B, calculated by mass, are: 49.6 parts of isocyanate, 11.4 parts of isocyanate prepolymer, 0.9 parts of catalyst, and 0.8 parts of defoaming agent.
[0092] The mass ratio of component A to component B is 1:0.95.
[0093] Comparative Example 3
[0094] The specific implementation of this comparative example is basically the same as that of Example 1, except that the composite polyol is a composition of propylene oxide-ethylene oxide copolyether glycol, polytetramethylene oxide ether glycol and polyurea polyol, and the mass ratio of the three is 8:1:0.4.
[0095] Comparative Example 4
[0096] The specific implementation of this comparative example is basically the same as that of Example 1, except that the composite polyol is a composition of propylene oxide-ethylene oxide copolyether glycol, polytetramethylene oxide ether glycol and polyurea polyol, and the mass ratio of the three is 3:2.5:1.
[0097] Comparative Example 5
[0098] The specific implementation of this comparative example is basically the same as that of Example 1, except that the number average molecular weight of propylene oxide-ethylene oxide copolyether glycol is 1900 Da, the hydroxyl value is 53 mgKOH / g, and the Voranol L190N product purchased from Dow Chemical.
[0099] Comparative Example 6
[0100] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the isocyanate prepolymer comprises the following steps, calculated by mass: S1: 5.5 parts of tripropylene glycol are vacuum dehydrated at 120°C for 2h, then 1.25 parts of polymethylene polyphenyl isocyanate are added, the mixture is kept warm at 85°C with stirring, the reaction is kept warm for 2h, the mixture is cooled to 60°C and discharged to obtain a pre-reaction material; S2: 10.6 parts of the pre-reaction material are added to 220 parts of deionized water, 0.45 parts of citric acid and 1.68 parts of succinic anhydride are added, the temperature is raised to 65°C and kept warm for 2h, a titanate coupling agent is added, the mixture is kept warm at 100rpm and stirred for 1h, the mixture is discharged after completion, and the mixture is obtained after dehydration.
[0101] Comparative Example 7
[0102] The specific implementation of this comparative example is basically the same as that of Example 1, except that: the preparation method of the isocyanate prepolymer comprises the following steps, calculated by mass: S1: 2.68 parts of tripropylene glycol are vacuum dehydrated at 120°C for 2 hours, then 1.95 parts of polymethylene polyphenyl isocyanate are added, the mixture is kept warm at 85°C with stirring, the reaction is kept warm for 2 hours, the mixture is cooled to 60°C and discharged to obtain a pre-reaction material; S2: 10.6 parts of the pre-reaction material are added to 220 parts of deionized water, 0.21 parts of citric acid and 0.95 parts of succinic anhydride are added, the temperature is raised to 65°C and kept warm for 2 hours, 0.1 parts of titanate coupling agent are added, the mixture is kept warm at 100rpm and stirred for 1 hour, the mixture is discharged after completion, and the mixture is obtained after dehydration.
[0103] Performance Evaluation
[0104] Mechanical properties: The chip potting adhesives prepared in the examples and comparative examples were tested for tensile strength, elongation at break and Shore hardness with reference to GB / T 528-2009 and GB / T 531-1999, respectively. The test values were averaged over 10 tests and recorded in Table 1.
[0105] Waterproofness: The chip potting glue prepared in the embodiment and the comparative example was cured to obtain a 2cm×2cm×0.2cm sample, and the sessile drop method was used to test the water contact angle on its surface. The test drop size was 2.5μL, the sealed ambient temperature was 30°C, the relative humidity was 45%, and the test time was 48h. The surface water contact angle at 48h was obtained and the test drop was retrieved to measure its retention rate (%). Retention rate (%) = water drop amount after test / water drop amount before test × 100%. The test value was the average value of 10 tests and recorded in Table 1.
[0106] Corrosion resistance: After curing the chip potting glue prepared in the embodiment and the comparative example, a 2cm×2cm×0.3cm sample was prepared, and immersed in a 5wt% NaCl solution for 400 hours. After 400 hours, the sample was taken out to ensure that the sample had no yellowing, blistering, cracking, corrosion or damage. If there was any, it was recorded as unqualified, otherwise it was qualified. The corrosion resistance qualified rate % = qualified number / 50×100%. 50 groups of samples were tested in each group and the test results were recorded in Table 1.
[0107] Aging resistance: After curing the chip potting glue prepared in the embodiment and the comparative example, a 2cm×2cm×0.2cm sample was prepared, and placed in a constant temperature and humidity chamber at 68±2°C and 75±3% relative humidity, and stored for 6 months. After 6 months, it was recorded whether the sample had yellowing, oxidation, cracking, blistering and hydrolysis damage. If so, it was recorded as unqualified, otherwise it was qualified. 50 samples were tested in each group, and the qualified rate of the samples was recorded and recorded in Table 1.
[0108] Table 1 Performance test results
[0109]
[0110] It can be seen from the examples and comparative examples of the present application and the data results in Table 1 that Examples 1 and 2 of the present application have obvious advantages over comparative examples 1 to 7 in terms of mechanical properties, waterproof properties, corrosion resistance, aging resistance and thermal stability. This is mainly due to the combined effect of the composite polyol composition, functional additives and prepolymers as well as other matching schemes specified in the present application. Comparative examples 1 to 7 did not adopt the technical scheme specified in the present application, resulting in obvious disadvantages in the above-mentioned performance tests, which further proves the necessity of the technical scheme specified in the present application for the technical effect of the present application and solving technical problems.
Claims
1. A water-resistant chip potting glue, characterized by: It is composed of component A and component B; the raw materials of component A, calculated by weight, are: 60-80 parts of compound polyol, 4-12 parts of plasticizer, 0.5-1.5 parts of antioxidant, 1.5-3 parts of leveling agent, 5-15 parts of filler, and 5-10 parts of auxiliary agent; The raw materials of component B are, by weight: 45-55 parts of isocyanate, 10-15 parts of isocyanate prepolymer, 0.5-1.2 parts of catalyst, and 1-1.5 parts of defoamer; The mass ratio of component A to component B is (1.1-1.2): (0.7-0.9); The composite polyol is a composition of propylene oxide-ethylene oxide copolyether glycol, polytetramethylene oxide ether glycol and polyurea polyol; The mass ratio of the propylene oxide-ethylene oxide copolyether glycol, polytetramethylene ether glycol and polyurea polyol is (4-5): (1.4-2): (0.5-1); The number average molecular weight of the propylene oxide-ethylene oxide copolyether diol is 3500-4800 Da; the hydroxyl value of the propylene oxide-ethylene oxide copolyether diol is 20-32 mgKOH / g; The number average molecular weight of the tetrahydrofuran ether diol is 1500-2200Da; the hydroxyl value of the tetrahydrofuran ether diol is 30-35mgKOH / g; The polyurea content of the polyurea polyol is 15-20%; The isocyanate is a composition of diphenylmethane diisocyanate and cyclohexylmethane diisocyanate; the mass ratio of diphenylmethane diisocyanate to cyclohexylmethane diisocyanate is (3-4): (0.8-1.2); The preparation method of the isocyanate prepolymer comprises the following steps: S1: vacuum dehydrating tripropylene glycol at 120-130° C. for 1.5-2 h, then adding polymethylene polyphenyl isocyanate, keeping warm at 80-90° C. with stirring, keeping warm for 2 h, cooling to 60-65° C. and discharging to obtain a pre-reaction material; S2: adding the pre-reaction material to deionized water, adding citric acid and succinic anhydride, then heating to 60-70° C. and keeping warm for 1.5-2 h, adding a titanate coupling agent, continuing to keep warm at 100-120 rpm with stirring for 0.5-1 h, discharging after completion, and obtaining the pre-reaction material after dehydration; The mass ratio of tripropylene glycol and polymethylene polyphenyl isocyanate is (2.6-2.8): (1.8-2.2); The mass ratio of the pre-reaction material, citric acid, succinic anhydride and titanate coupling agent is (10-12): (0.4-0.6): (1.5-2): (0.2-0.25); The catalyst is dibutyltin dilaurate or stannous octoate; The auxiliary agent is methyl hydrogen polysiloxane; the hydrogen content of the methyl hydrogen polysiloxane is 0.8-2%.
2. The water-resistant chip potting adhesive according to claim 1, characterized in that: The mass ratio of the complex polyol, plasticizer and filler is (65-75): (6-10): (8-14); the plasticizer is at least one of dioctyl phthalate, trioctyl citrate and triethyl citrate; the antioxidant is at least one of antioxidant 1010, antioxidant 1076 and antioxidant 1035.
3. The water-resistant chip potting adhesive according to claim 2, characterized in that: The plasticizer is dioctyl phthalate or triethyl citrate.
4. The water-resistant chip potting adhesive according to claim 3, characterized in that: The filler is a composition of sericite powder and alumina; the mass ratio of the sericite powder to alumina is (2-3): (1.2-1.6).
5. The water-resistant chip potting adhesive according to claim 4, characterized in that: The average particle size of the sericite powder is 1-2 μm; the average particle size of the aluminum oxide is 20-35 nm.
6. The water-resistant chip potting adhesive according to claim 5, characterized in that: The methyl hydrogen polysiloxane is a composition of methyl hydrogen polysiloxane with a hydrogen content of 0.9-1% and 1.55-1.8%; the mass ratio of the methyl hydrogen polysiloxane with a hydrogen content of 0.9-1% and 1.55-1.8% is (4-4.2): (1-1.2).
7. The water-resistant chip potting adhesive according to claim 6, characterized in that: The defoamer is any one of the organosilicon defoamers.
8. A method for preparing the water-resistant chip potting adhesive according to any one of claims 1 to 7, characterized in that: The specific steps include: S1: Weigh the raw materials required for component A and component B respectively, mix and stir them evenly in different mixing containers at a temperature of 25~35℃ and a stirring speed of 60~80rpm to obtain component A and component B; S2: Mix component A and component B in a clean container according to the mass ratio, stir them evenly at a temperature of 25~35℃ and a stirring speed of 200~250rpm. After mixing evenly, place the mixture in a vacuum environment for degassing treatment, the vacuum degree is -0.09~-0.10MPa, and the degassing time is 10~15min; S3: After degassing, pour the mixture into the chip components to be encapsulated, heat it to 70~85℃ and cure it for 3~4h to obtain the chip encapsulation glue.
Citation Information
Patent Citations
Silanol-based bicomponent waterborne polyurethane wood adhesive and preparation method thereof
CN107446538A
Polyurethane pouring sealant and preparation method thereof
CN115595108A